2018
DOI: 10.1007/s10508-017-1139-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Disorders of Sex Development/Intersex Conditions in Iranian Culture: Congenital Adrenal Hyperplasia, 5-α Reductase Deficiency-Type 2, and Complete Androgen Insensitivity Syndrome

Abstract: Sixty-one patients (22 patients with congenital adrenal hyperplasia [CAH] with a mean age of 14.86 years [range, 5-23], 20 patients with 5-α reductase deficiency type 2 [5α-RD-2] with a mean age of 19.5 years [range, 5-29], and 19 patients with complete androgen insensitivity syndrome [CAIS] with a mean age of 18.26 years [range, 5-28]) were evaluated using the Kiddie Schedule for Affective Disorders and Schizophrenia, the Structured Clinical Interview for DSM-IV Axis I, Axis II, and the Global Assessment Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The current review indicates that females with CAH more often than the general population define themselves as nonheterosexual, which could have clinical implications. Other research findings pertaining research on CAH have shown psychologic and psychiatric problems to be more frequent in this group, particularly anxiety or depressive disorders and drug/alcohol abuse (Hochberg et al, 1987;Falhammar et al, 2014a;Engberg et al, 2015;Pasterski et al, 2015;Daae et al, 2018;Khorashad et al, 2018). In addition, some females with CAH will go through feminizing surgery (Crouch et al, 2008) and/or may show symptoms of androgen excess, e.g., hirsutism (Meyer-Bahlburg et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The current review indicates that females with CAH more often than the general population define themselves as nonheterosexual, which could have clinical implications. Other research findings pertaining research on CAH have shown psychologic and psychiatric problems to be more frequent in this group, particularly anxiety or depressive disorders and drug/alcohol abuse (Hochberg et al, 1987;Falhammar et al, 2014a;Engberg et al, 2015;Pasterski et al, 2015;Daae et al, 2018;Khorashad et al, 2018). In addition, some females with CAH will go through feminizing surgery (Crouch et al, 2008) and/or may show symptoms of androgen excess, e.g., hirsutism (Meyer-Bahlburg et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…No participants were diagnosed with adjustment disorders, attention-deficit and disruptive disorders, substance-related disorders, eating disorders, or psychotic disorders. Khorashad et al (2018) also found that, among both adults and children, the DSD groups had significantly more mental health issues than comparison groups (Iranian general population).…”
Section: Resultsmentioning
confidence: 80%
“…Four studies assessed for psychopathology in participants with 46,XY DSD using psychodiagnostic interviews. In Iran, Khorashad et al (2018) assessed lifetime episodes of psychopathology in adults and children with CAIS and 5α-RD (mean age = 18.9) using the Structured Clinical Interview for DSM -IV (SCID; First et al, 1997) and the Kiddie Schedule for Affec-tive Disorders and Schizophrenia (K-SADS; Lauth et al, 2010). All of the patients with CAIS identified as female, while 55 percent of patients with 5α-RD identified as male and 45 percent identified as female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and affective disorders (16.4% and 27.9%, respectively) were the most common disorders that could cause fear of sexual relationship, premature ejaculation, impotence, nocturia, poor stream and eventually prostatitis (18,19). Therefore, early diagnosis and evaluation of this problem will reduce the concern of parents and children (20).…”
Section: Discussionmentioning
confidence: 99%